Pelaksanaan Pembatalan Sertifikat Hak Milik Atas Tanah Oleh Badan Pertanahan Nasional Berdasarkan Putusan Pengadilan Tata Usaha Negara - Riski Apriani; Abd. Rais Asmar (Alauddin Law Development Journal (ALDEV), 2022)
This research is the result of qualitative field research to answer legal issues proposed by the author to be investigated using data collection techniques, namely, descriptive data in the form of written or spoken words from people and actors who can be observed. analysis is temporary and will always evolve or change as long as researchers go down and leave the field. From the research that has been done, the authors get the following results: That in the implementation of the cancellation of the shm after a PTUN decision which is inward in nature can only be carried out by the National Land Agency with due regard to this decision, related to how the binding legal force is in canceling the ownership certificate by BPN based on the PTUN decision, BPN cannot automatically cancel the ownership certificate, one of the conditions that needs to be considered is related to canceling the ownership certificate if the decision issued by the PTUN is a decision that is inconsistent both in the verdict and the result of the decision, so that only then can the ownership certificate be canceled by BPN. In resolving land cases, the names of disputes, conflicts and land cases are distinguished according to the regulation of Permenag No.11 of 2016